A Libras como artefato cultural linguístico no ambiente familiar do sujeito surdo - Melgueiro, Maria Neide Gomes (Brasil, 2023)
This research presents Libras as a Linguistic Cultural Artifact in the Family Environment of the Deaf Subject, in which it promotes the knowledge and importance of sign language in the family environment and the relationship of the hearing family with the deaf person, where it reveals the linguistic cultural ignorance that involves the deaf; in addition to the struggle undertaken by the deaf community to have the right to information and access to knowledge through sign language. With the general objective to know the importance of Libras as a linguistic cultural artifact in the family environment of the deaf person, having as theorists the authors Strobel (2008) with linguistic and family cultural artifacts, Sacks (2010) with reports of families and deaf people showing their reality, and Gesser (2009) where she presents the importance of sign language for the knowledge and learning of the deaf person. A bibliographic methodology was used with texts, articles and books and qualitative methods such as a small questionnaire with mothers who have deaf children in the Letras Libras course, whether it is a transforming contribution in a given social and cultural reality. Finally, the results found through the parents of deaf children realize the importance of sign language in the family environment and that through communication they begin to have access and a new language learning in their family environment.